Sintagma Dalam Cerpen “Jaket“ Ayah Karya Eep Saefulloh Fatah Dengan Perspektif Semiotik Sastra - Andika Hendra Mustaqim (Wanastra: Jurnal Bahasa dan Sastra, 2018)
The goal of this research is exploring the syntagm in the short story Jaket Ayah by Eep Saefulloh Fatah. The research method in this research is content analysis. The result and the analysis of the research, the research finds some syntagm elements, the first syntagm is the politician which consist the arrogant political party, the magician, full of theatrics, the traitorous, the tactics, and many promises. Another syntagm is a political party consisting of a cadre crisis, a candidate for leader, a clean person, and a regional head election. Other syntagm is dowry which related to political costs, consolidation and coordination, and extortion. The other syntagm was the other candidate bupati namely imaging, campaign, and famous. The most syntagm is the family which consist attention, affection, and build the future. Next, two very prominent signs are the jacket and the savings. The jacket is a witness in every political event involving the father. Savings funds should be used for the best interests that have been planned from the beginning. A savings fund should be a chapter that must determine a comforting new life rather than troubling and worrying. "Jaket Ayah" was written by Eep Saefulloh Fattah who is a political observer who loves to write stories.